Antioxidant composition Twendee X may improve long COVID symptoms - You, Fukka (Brain Supplement, 2022)
As the SARS-CoV-2 pandemic rages, long-lasting sequelae (long COVID) are a problem in many countries around the world. At present, there is no effective and evidence-based treatment. COVID-19 has been shown to cause oxidative stress in the body, which is responsible for the amplification and persistence of cytokine storms and blood coagulation abnormalities in the causative SARS-CoV-2 infection. Therefore, it was hypothesized that the administration of an antioxidant supplement would provide symptomatic relief. TIMA Tokyo Ltd. conducted a web-based survey of people suffering from long COVID and participants were provided with the antioxidant composition supplement Twendee X free of charge. The survey asked participants to self-report the severity of the eight typical adverse reactions (fatigue, breathing difficulty, chest pain, smell and taste disorders, headache, brain fog, joint pain, and dizziness) on a six-point scale at the time of participation and one month after taking Twendee X. In this interim report, severity scores for all symptoms except joint pain were significantly reduced. In particular, when the scores of the relatively severe participants who responded with scores 3-5 were averaged, the scores were less than half of the pre-taking scores in all cases. The results suggest that the symptoms of long COVID are caused by elevated systemic oxidative stress, and that antioxidants may help prevent or treat the reduction.Brain Supplement 2022; 4: 7-12